Berberine Attenuates Cerebral Ischemia-Reperfusion Injury Induced Neuronal Apoptosis by Down-Regulating the CNPY2 Signaling Pathway - Zhao, Lina; Li, Huanming; Gao, Qian; Xu, Jin; Zhu, Yongjie; Zhai, Meili; Zhang, Peijun; Shen, Na; Di, Yanbo; Wang, Jinhui; Chen, Tie; Huang, Meina; et al. (Frontiers in Pharmacology, 2021)
Berberine (BBR) has a neuroprotective effect against ischemic stroke, but its specific protective mechanism has not been clearly elaborated. This study explored the effect of BBR on the canopy FGF signaling regulator 2 (CNPY2) signaling pathway in the ischemic penumbra of rats. The model of cerebral ischemia-reperfusion injury (CIRI) was established by the thread embolization method, and BBR was gastrically perfused for 48 hours or 24 hours before operation and 6 hours after operation. The rats were randomly divided into four groups: the Sham group, BBR group, CIRI group, and CIRI+BBR group. After 2 hours of ischemia, followed by 24 hours of reperfusion, we confirmed the neurologic dysfunction and apoptosis induced by CIRI in rats (P<0.05). In the ischemic penumbra, the expression levels of CNPY2-regulated endoplasmic reticulum stress-induced apoptosis proteins (CNPY2, glucose-regulated protein 78 (GRP78), double-stranded RNA-activated protein kinase-like ER kinase (PERK), C/EBP homologous protein (CHOP), and Caspase-3) were significantly increased, but these levels were decreased after BBR treatment (P<0.05). To further verify the inhibitory effect of BBR on CIRI-induced neuronal apoptosis, we added an endoplasmic reticulum-specific agonist and a PERK inhibitor to the treatment. BBR was shown to significantly inhibit the expression of apoptotic proteins induced by endoplasmic reticulum stress agonist, while the PERK inhibitor partially reversed the ability of BBR to inhibit apoptotic protein (P<0.05). These results confirm that berberine may inhibit CIRI-induced neuronal apoptosis by downregulating the CNPY2 signaling pathway, thereby exerting a neuroprotective effect.